The Validation and Extension of Fiedler's Theory of Leadership Effectiveness - Hill, Walter A. (Academy of Management Journal, 1969)
The author tests in a large electronics firm and in a fairly large hospital, the contingency model of leadership effectiveness in interacting and coacting groups.